A multimodal Pepstatin A peptide-based nanoagent for the molecular imaging of P-glycoprotein in the brains of epilepsy rats. (January 2016) - Yu, Xiangrong; Wang, Jianhong; Liu, Jiansheng; Shen, Shun; Cao, Zhonglian; Pan, Jiawei; Zhou, Shuyi; Pang, Zhiqing; Geng, Daoying; Zhang, Jun
Abstract: Regional overexpression of the multidrug transporter P-glycoprotein (P-gp) in epileptic brain tissues may lower antiepileptic drugs concentrations at the target site and contribute to pharmacoresistance in refractory epilepsy. However, few techniques are available to quantitate the level of P-gp expression noninvasively in vivo. In this study, we developed a nanoagent by conjugating superparamagnetic iron oxide nanoparticles with a near infrared probe and the targeting element Pepstatin A, a peptide with specific affinity for P-gp. In a rat model of epilepsy, the nanoagent was readily and selectively accumulated within epileptogenic cerebral regions, which were detectable by both magnetic resonance imaging and optical imaging modalities. This P-gp-targeted nanoagent could be used not only in the molecular imaging of P-gp expression changes in seizure-induced regional, understanding the mechanisms of P-gp disorders, and the prediction of refractory epilepsy, but also in targeted therapies with P-gp modulators.